Zebrafish Tric-b is required for skeletal development and bone cells differentiation - Tonelli, Francesca; Leoni, Laura; Daponte, Valentina; Gioia, Roberta; Cotti, Silvia; Fiedler, Imke A. K.; Larianova, Daria; Willaert, Andy; Coucke, Paul J.; Villani, Simona; Busse, Björn; Besio, Roberta; et al. (Frontiers in Endocrinology, 2023)
Trimeric intracellular potassium channels TRIC-A and -B are endoplasmic reticulum (ER) integral membrane proteins, involved in the regulation of calcium release mediated by ryanodine (RyRs) and inositol 1,4,5-trisphosphate (IP3Rs) receptors, respectively. While TRIC-A is mainly expressed in excitable cells, TRIC-B is ubiquitously distributed at moderate level. TRIC-B deficiency causes a dysregulation of calcium flux from the ER, which impacts on multiple collagen specific chaperone and modifying enzyme activity, leading to a rare form of osteogenesis imperfecta (OI Type XIV). The relevance of TRIC-B on cell homeostasis and the molecular mechanism behind the disease are still unknown. In this study, we exploited zebrafish to elucidate the role of TRIC-B in skeletal tissue. We demonstrated, for the first time, that tmem38a and tmem38b genes encoding Tric-a and -b, respectively are expressed at early developmental stages in zebrafish, but only the latter has a maternal expression. Two zebrafish mutants for tmem38b were generated by CRISPR Cas9, one carrying an out of frame mutation introducing a premature stop codon (tmem38b-/-) and one with an in frame deletion that removes the highly conserved KEV domain (tmem38bΔ120-7/Δ120-7). In both models collagen type I is under-modified and partially intracellularly retained in the endoplasmic reticulum, as described in individuals affected by OI type XIV. Tmem38b-/- showed a mild skeletal phenotype at the late larval and juvenile stages of development whereas tmem38bΔ120-7/Δ120-7 bone outcome was limited to a reduced vertebral length at 21 dpf. Caudal fin regeneration study pointed towards impaired activity of osteoblasts and osteoclasts associated with mineralization impairment. Our data support the requirement of Tric-b during early development and in bone cell differentiation.